Barriers to and facilitators of employment : perspectives of persons with severe communication disabilities and specialised recruitment agents - Dada, Shakila (University of Pretoria, 2022)
Thesis (PhD (Augmentative and Alternative Communication))--University of Pretoria, 2021.